Development of the Database for Environmental Sound Research and Application (DESRA): Design, Functionality, and Retrieval Considerations. (14th June 2010) - Gygi, Brian; Shafiro, Valeriy
Abstract : Theoretical and applied environmental sounds research is gaining prominence but progress has been hampered by the lack of a comprehensive, high quality, accessible database of environmental sounds. An ongoing project to develop such a resource is described, which is based upon experimental evidence as to the way we listen to sounds in the world. The database will include a large number of sounds produced by different sound sources, with a thorough background for each sound file, including experimentally obtained perceptual data. In this way DESRA can contain a wide variety of acoustic, contextual, semantic, and behavioral information related to an individual sound. It will be accessible on the Internet and will be useful to researchers, engineers, sound designers, and musicians.